PENGEMBANGAN PEMBELAJARAN BERBANTUAN KOMPUTER (PBK) MATA KULIAH ILMU PENDIDIKAN DI JURUSAN PENDIDIKAN AGAMA ISLAM (PAI) FAKULTAS TARBIYAH IAIN PORWOKERTO - Hardiman Hardiman (Jurnal Pendidikan Agama Islam, 2014)
The study at (1) developing the software of computer-assisted instruction (CAI) of Eductional Science Cource as one of the alternatives of learning source and teaching media, useable to solve students learning problems, especially those of limited learning source, and to achieve student effectiveness, efficiency and interest and (2) revealing its feasibility to be implemented.The number of respondent involved in all phases of this study was 44 consisting of 2expert of non Educational Science course, 2 lecturers of Educational Science Cource, 3 individually learning students, 8 lecturers of small grup learning and 29 studentt of large group learning. The data collected in this study included the accuracy of the design and media, effectiveness of contents of teaching, effectiveness of teaching material and revies by 2 experts of non-Educational Science cource and 2 lecturers of Educatioal Science Cource, questionnaires for student and participant observation. The data ware analyzed using the descriptive qualitative technique.The findings showed that the software developed for the CAI of Educational Science Cource conform to the syllabi of Educational Science Cource and thereforce it could be used as teaching media. CAI is an effective strategy for teching objectives attainment; it is a strategy which is very efficient relative to the shortage instructors, time allocation, and learning resources. As part of teaching strategies, CAI is very attractive.